One-dimensional microwave photonic crystals - Usanov, D. A.; Nikitov, S. A. (Sergei Apollonovich), 1955-; e uthor; Ponomarev, D. V. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
'Explores theoretical and experimental studies of the properties of one-dimensional photonic crystals'--
One-dimensional microwave photonic crystals based on rectangular waveguides -- Microwave photonic crystals based on planar transmission lines -- Possibilities of controlling the characteristics of microwave photonic crystals by means of electric and magnetic fields -- Applications of microwave photonic crystals.
Includes bibliographical references and index.
Keywords: Photonic crystals; Wave guides; Microwave devices